Perancangan Sistem Informasi Akuntansi Penjualan Obat Menggunakan Microsoft Visual Studio 2010 Di Klinik Utama Bunda Nanda - Rani, Rani Nurdianti; Tina, Tina Yusepa; Karyadi, Karyadi; Falaah, Falaah Abdussalaam (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Klinik Utama Bunda Nanda is one of the maternity homes that provides pharmaceutical services which is marked by the presence of a pharmacy in it. The purpose of this research is to develop a drug sales accounting information system design using Microsoft Visual Studio 2010 and MySQL database. In this study, the authors use qualitative methods with data collection methods literature study, interview data or observation. And the system development method used is the waterfall. From the results of the study, it was found that the problem was that the management of drug sales data was still manual so that it was prone to errors, including the process of searching for data or preparing reports that took a relatively long time, and the information presented was less accurate. The author hopes that the design of a drug sales information system can make it easier for employees to manage sales data and can minimize errors that may occur.